2018
DOI: 10.51723/ccs.v28i03/04.283
|View full text |Cite
|
Sign up to set email alerts
|

Planejamento da Assistência em Enfermagem: proposta para implementação de um instrumento administrativo-assistencial

Abstract: Introdução: Tendo como base os meios e normas que regem a atividade do enfermeiro e a correta aplicação da Sistematização da Assistência da Enfermagem como parte do planejamento de um cuidado associado ao conhecimento científico e a necessidade de organização, foi elaborado um instrumento capaz de facilitar, otimizar e oferecer informações pertinentes à assistência do indivíduo em uma Unidade de Cuidados Intermediários Neonatais – UCIN. Sua utilização serve ainda como base para a elaboração de dados estatístic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…In the NSs, care and managerial work processes are predominant (21)(22)(23)(24)(25) . An observational study conducted with nurses of critical units aimed at pediatric and adult patients in a University hospital found this evidence: it identified that, of the 2,295 activities performed by nursing professionals, 61.1% were assistance and 18.3% managerial (26) .…”
Section: Discussionmentioning
confidence: 99%
“…In the NSs, care and managerial work processes are predominant (21)(22)(23)(24)(25) . An observational study conducted with nurses of critical units aimed at pediatric and adult patients in a University hospital found this evidence: it identified that, of the 2,295 activities performed by nursing professionals, 61.1% were assistance and 18.3% managerial (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Nos SEs, os processos de trabalho assistencial e gerencial são predominantes (21)(22)(23)(24)(25) . Evidência disso se encontra em estudo observacional realizado com enfermeiros de unidades críticas, destinadas a pacientes pediátricos e adultos, de um hospital universitário: identificou-se que, das 2.295 atividades executadas por profissionais de enfermagem, 61,1% foram assistenciais e 18,3% gerenciais (26) .…”
Section: Discussionunclassified
“…Thus, it is one of the management tools for monitoring and evaluating the productivity and quality of care provided to patients in hospital environments (14) . However, the use of these technologies is the target of much criticism, as they are considered bureaucratic, since, currently, there are other digital technologies (such as Web applications, applications for mobile phones or management tablets, planning software, among others) that they provide the same resources in a more organized, easily accessible and democratic way, helping in planning, decision-making, management control, quality of care and communication between professionals (15) . It is also worth noting that, in an investigation carried out in Portugal on the usefulness of ICT in nursing practice, the factors that conditioned the appreciation of SClí-nico®, which in this country is the technology that incorporates items that translate the nursing process and the nurses' work plan, referred to the complexity and inadequacy of the technology to some work contexts, the lack of knowledge about the technology, as well as the time required to perform the records (16) .…”
Section: Discussionmentioning
confidence: 99%